Unravelling the 9th May Incident: The Impact of Post-9/11 Pakistan-US Alliance on Pakistan’s Security - Ahmad, Ashfaq; Hussain, Safdar (Annals of Human and Social Sciences, 2023)
The objective of the study is to examine the aftermath of Pakistan’s alliance with the U.S. following 9/11, focusing on its impact in creating divisions among the populace and institutions, as evidenced by the events of May 9, 2023. It highlights how Pakistan’s compromises for economic and military aid have undermined its autonomy, exacerbating security challenges, including rising grievances among populace. Through qualitative analysis, the study uncovers the incident’s origins in deep-seated grievances and perceived U.S. interference, underscoring its exploitation for political gains. The 9th May incident, a manifestation of deeply-rooted grievances, emerged as a reaction to perceived U.S. interference in Pakistan’s internal affairs, exploited by political leader for their own gains. The study emphasizes the adverse effects of such alliances on Pakistan’s internal affairs and security, stressing the need for diplomatic strategies prioritizing national stability. Its findings advocate for future diplomatic approaches mindful of these alliances’ impact on Pakistan’s autonomy, aiming for enhanced national stability while addressing security implications.